Project Report on Bandwidth Efficient Video Multicasting in Multiradio Multicellular Wireless Networks - ASHVIN SHENVI, MANU B, RAKESH H S and VASHIST S (2010)
INTERNAL GUIDE: ANATHA LAKSHMI E, MVJCE
Keywords: Multicellular Wireless Networks